Primary lymphoma of the lingual tonsil: a case report - Sıdıka Deniz Micozkadıoğlu; Cem Özer; Emine Tuba Canbolat (Turkish Archives of Otorhinolaryngology, 2010)

(untitled)
Extranodal non-Hodgkin lymphomas of the head and neck are rare. Most of the oral cavity lymphomas originate from Waldeyer ring and present as a mass in the oropharynx or nasopharynx. Tongue base is the most common location. 57- year-old male patient presented to our clinic with a painless swelling in the neck which had grown for two months. He had dysphagia. Physical examination revealed an eryhtematous mass resulted tonsil hypertrophy and asymmetry in the tongue base. In the neck there was a palpable jugulodigastric lymphadenopathy. Computed tomography of the patient revealed a mass from tongue base to vallecula and multiple lymphadenopathies in the cervical chain. The patient was diagnosed as lymphoma. As a result since lingual tonsil lymphomas are rare tumors therefore they should be thought in the differential diagnosis of oral cavity masses.